MODEL PEMBELAJARAN BAHASA ARAB DI SMPUT BUMI KARTINI DALAM MENINGKATKAN KEMAMPUAN SISWA BERBAHASA ARAB - Rahmawati, Ana; Laila, Azzah Nor (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2019)
This study aims to describe the Arabic learning model in SMP Kartini Bumi in an effort to improve the ability of Arabic-speaking students, besides that this study also attempts to explain some of the inhibiting factors and factors that support the implementation of intensive Arabic language programs (extracurricular activities) carried out in the boarding environment school in the Bumi Kartinid SMPUT in an effort to improve the ability of the Arabic language students in addition to the Arabic subjects that they actually get in learning in the classroom as subjects of local content. The focus of the problem in this study included: (1) the model for implementing Arabic learning at SMP Kartini Bumi, (2) supporting factors and inhibiting factors for the implementation of intensive Arabic language programs. This research uses descriptive analytical method by collecting data from interviews, observation and documentation, the data is collected and analyzed by reducing data, presenting data and drawing conclusions. From the results of the study it was found that the Arabic learning model in SMPUT Bumi Kartini used a direct learning model that is the teacher conveying the content of the subject matter in a structured and structured manner, directing the activities of the students, and maintaining the focus of academic achievement. the forms are in the form of Arabic (local content) and school extracurricular subjects. Extracurricular activities aim to support the improvement of students' ability to speak Arabic which is implemented in intensive classroom activities in Arabic, and Bilingual Club. Language intensive extracurricular activities are held every day after school, even though these activities are carried out on school boarding, but the intensive class is included in the extracurricular activities of the school. The main purpose of the direct learning model is to maximize the use of student learning time. Which in practice students practice it using Arabic in their daily lives in the boarding school environment. The supporting factor remains the implementation of intensive language classes is the existence of adequate infrastructure and students who are very enthusiastic in attending intensive language classes. While the inhibiting factor is the lack of teachers and the lack of varied learning media used in the learning process.Â Keywords: learning model, Arabic, SMPUT Kartini